THE INFLUENCE OF GREEN MARKETING MIX ON CONSUMER PURCHASING DECISIONS ON TUPPERWARE PRODUCTS BY THE PEOPLE OF LHOKSEUMAWE CITY - Cut Intan Julia; T. Edyansyah; Mariyudi; Khairina AR (RADJA PUBLIKA, 2023)
Issues regarding the environment have become a problem for the wider community and have resulted in changes in consumer preferences to become more inclined to use environmentally friendly products. This is an opportunity for companies to make environmentally friendly products and use more environmentally friendly raw materials. The aim of this research is to analyze and determine the influence of green products, green place, green price and green promotion on purchasing decisions for Tupperware products by the people of Lhokseumawe City. This type of research is quantitative research with a consumer population in Lhokseumawe City. There were 100 respondents, taken using purposive sampling technique. The data source comes from primary data obtained through distributing questionnaires. The data analysis techniques used are descriptive analysis methods and multiple linear regression analysis, classical assumption testing, instrument testing (validity and reliability), hypothesis testing and coefficient of determination and correlation testing and analyzed with the help of the SPSS version 26 application program. The results of this research show that simultaneously green product, green price, green place and green promotion have a positive and significant effect on consumer purchasing decisions for Tupperware products by the people of Lhokseumawe City. Meanwhile, partially the green product variable does not have a significant effect on purchasing decisions. However, the variables green price, green place and green promotion have a significant influence on consumer purchasing decisions for Tupperware products by the people of Lhokseumawe City. Green promotion is the most dominant variable that influences consumer purchasing decisions with a t value of 6.467.